The Effect of Using Short Stories on Students’ English Reading Comprehension - Fani Apriliani; Nurdin Noni; Munir Munir (Journal of Excellence in English Language Education, 2026)
This study aimed to determine the effect of using short stories on students’ reading comprehension. A quantitative method with a pre-experimental design was used, involving 30 eighth-grade students selected through random sampling. A reading test based on short stories was administered to assess five comprehension indicators: main idea, detailed information, inference, vocabulary, and reference. A pre-test was conducted to measure students’ initial abilities, followed by a treatment through short story-based instruction, and a post-test was conducted to measure improvement. The average pre-test score was 52.86, while the post-test average increased to 76.16. A paired sample t-test showed a significant difference (p = 0.000 < 0.05), indicating that the treatment had a positive effect. Among all indicators, the most notable improvement was in reference (from 46.67% to 90%), followed by vocabulary (from 55% to 84%). These results suggest that short stories effectively support the development of students’ reading comprehension, especially in helping them identify references and understand vocabulary in context. Overall, the use of short stories not only improved comprehension scores but also contributed to more consistent performance among students. Therefore, short stories can be considered a beneficial tool in teaching reading comprehension to eighth-grade students at SMPN 26 Makassar.